Dance Tradition of the Macedonian Diaspora in Serbia (Following the Research of Ethnochoreologist Mihailo Dimovski in Glogonj and Jabuka) - Kostov (FYR Macedonia), Stojanche (Bulletin of the Institute of Ethnography SASA, 2018)
The Macedonian minority in Serbia has always attracted great attention from Macedonian researchers, especially during the 70’s and 80’s of the 20th century. The interest, except in historical, philological and cultural terms, was also present regarding the dance tradition. This text will deal with the transfer, nurturing and maintenance of the dance tradition among the Macedonians in Glogonj and Jabuka, according to examples from the ethnochoreologist Mihailo Dimovski’s research. He had taken an interest in Macedonian minority in 1973, whereupon he performed an extensive ethnochoreological research and collected extensive material. His records, which are in the Archive of the Institute of Folklore "Marco Cepenkov" – Skopje, have not been completely published yet. Thus, the text will be an attempt to present his findings regarding the dance tradition of the Macedonian diaspora in the said period. Key words: folk dances, Macedonian minority, ethnochoreological research, archive materials